The Survival of Human Intervertebral Disc Nucleus Pulposus Cells under Oxidative Stress Relies on the Autophagy Triggered by Delphinidin - Md Entaz Bahar; Jin Seok Hwang; Trang Huyen Lai; June-Ho Byun; Dong-Hee Kim; Deok Ryong Kim (MDPI AG, 2024)
Delphinidin (Delp), a natural antioxidant, has shown promise in treating age-related ailments such as osteoarthritis (OA). This study investigates the impact of delphinidin on intervertebral disc degeneration (IVDD) using human nucleus pulposus cells (hNPCs) subjected to hydrogen peroxide. Various molecular and cellular assays were employed to assess senescence, extracellular matrix (ECM) degradation markers, and the activation of AMPK and autophagy pathways. Initially, oxidative stress (OS)-induced hNPCs exhibited notably elevated levels of senescence markers like p53 and p21, which were mitigated by Delp treatment. Additionally, Delp attenuated IVDD characteristics including apoptosis and ECM degradation markers in OS-induced senescence (OSIS) hNPCs by downregulating MMP-13 and ADAMTS-5 while upregulating COL2A1 and aggrecans. Furthermore, Delp reversed the increased ROS production and reduced autophagy activation observed in OSIS hNPCs. Interestingly, the ability of Delp to regulate cellular senescence and ECM balance in OSIS hNPCs was hindered by autophagy inhibition using CQ. Remarkably, Delp upregulated SIRT1 and phosphorylated AMPK expression while downregulating mTOR phosphorylation in the presence of AICAR (AMPK activator), and this effect was reversed by Compound C, AMPK inhibitor. In summary, our findings suggest that Delp can safeguard hNPCs from oxidative stress by promoting autophagy through the SIRT1/AMPK/mTOR pathway.